Odpowiedzi

2010-03-10T16:56:56+01:00
A) 4(x+3)=5x-19
4x+12=5x-19
4x-5x=-19-12
-x=-31/:(-1)
x=31

b)2(2m-3)+2m=5(3- m) +1
4m-6+2m=15-5m+1
4m+2m+5m=15+1+6
11m=22/:11
m=2

c)2 + 3m= 5 - 5m
3m+5m=5-2
8m=3/:8
m=0,375

Mam nadzieję że pomogłam. Pozdrawiam ;)
1 1 1
Najlepsza Odpowiedź!
2010-03-10T16:58:03+01:00
A) 4(x+3)=5x-19
4x + 12 = 5x - 19
4x - 5x = -19 - 12
-x = - 31 ÷ (-1)
x = 31
b) 2(2m-3)+2m=5(3- m) +1
4m - 6 + 2m = 15 - 5m + 1
6m - 6 = 16 - 5m
6m + 5m = 16 + 6
11m = 22 ÷ 11
m = 2
c) 2 + 3m= 5 - 5m
3m + 5m = 5 - 2
8m = 3 ÷ 8
m = 3/8
2 5 2
  • Użytkownik Zadane
2010-03-10T17:01:25+01:00
A) 4(x+3)=5x-19
4x+12=5x-19 |-4x
12=x-19 | +19
x=31
b)
2(2m-3)+2m=5(3- m) +1
4m-6+2m=15-5m+1 |+5m
11m-6=16|-6
11m=10
m=0,9
c)2 + 3m= 5 - 5m|+5m
2+8m=5|-2
8m=3
m=2,6

























1 1 1